The Effect of Dietary Alpinia officinarum (Hance) Supplementation in Bovns-type Chicks - Seddeag, Mawahib; Madawe, Gadallah; El Badwi, S.M.A.; Bakhiet, A.O. (International Journal of Poultry Science, 2010)
The galangal (the rhizome of Alpinia officinarum, Hance) is popular as a traditional herbal medicine. The present study investigates the effect of diet containing 2%, 5% and 10 % of A. officinarum (Hance) on the biochemical, haematological and histological parameters in Bovans-type chicks treated for 4 weeks. The body weight of the chicks revealed that feeding levels of 2, 5 and 10% dietary A. officinarum was significantly decreased (p